THE KOIN JAGAT GAME ON THE DESTRUCTION OF PUBLIC FACILITIES IN INDONESIA: A CDA STUDY - Andini Kurnia Firdaus; Kiki Nurrizqiyyah; Naufal Maulana Faza; Devi Mulatsih; Dian Farijanti (Lire Journal (Journal of Linguistics and Literature), 2025)
This study aims to analyze the impact of the coin jagat game phenomenon on the social life of Indonesian society using the Critical Discourse Analysis (CDA) approach. The study focuses on the narrative related to the phenomenon of Koin Jagat and the response given by the government. The urgency of this research lies in understanding the impact of digital technology on social behavior, including in education involving students. According to Van Dijk’s theory, media language has an important role in shaping public opinion. The phenomenon resulting from the existence of the Koin Jagat game is the cause of the destruction of public facilities and disruption of social order. By understanding the phenomenon, educational institutions can develop a better digital literacy curriculum. This research uses a qualitative approach with a text analysis method sourced from national media online news data. The data collected is analyzed using Van Dijk’s theory which includes analysis of the macrostructure, superstructure, and microstructure of the text.